2020
DOI: 10.33541/jet.v6i1.1061
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Edmodo use as a Learning Tool

Abstract: Due to the development of technology, teachers are expected to integrate technology into the classroom to engage the Z Generation students. Edmodo is a popular online learning platform that has now been widely used as a learning management system in blended learning or just as a supplementary tool. This study aims at investigating students' perceptions of Edmodo as a learning tool. Involving 47 students of the English department of Universitas Kristen Indonesia, data were collected employing a questionnaire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Edmodo is an educational site that allows students to access uploaded learning content (learning materials, learning links and videos, assignments, and grade notifications) by teachers, and makes it easier for teachers and students to communicate in an online classroom environment (Rifai, 2017). Previous research stated that Edmodo can cause students to participate more in learning, Edmodo is a tool that needs to be introduced to students because it is more productive and allows students to easily interact in the world of education (Siahaan, 2020). It can be concluded that Edmodo is a social network for learning based on the Learning Management System (LMS).…”
Section: Technology and Education Systemmentioning
confidence: 99%
“…Edmodo is an educational site that allows students to access uploaded learning content (learning materials, learning links and videos, assignments, and grade notifications) by teachers, and makes it easier for teachers and students to communicate in an online classroom environment (Rifai, 2017). Previous research stated that Edmodo can cause students to participate more in learning, Edmodo is a tool that needs to be introduced to students because it is more productive and allows students to easily interact in the world of education (Siahaan, 2020). It can be concluded that Edmodo is a social network for learning based on the Learning Management System (LMS).…”
Section: Technology and Education Systemmentioning
confidence: 99%
“…In order adopt and develop I encourage educators to think about using the Edmodo-RASE concept as a paradigm for creating a safe atmosphere for pupils to learn in. [20].…”
Section: Research Implementationmentioning
confidence: 99%
“…They also have poor internet connections, limited activities, and are easily bored. Furthermore, study by Siahaan (2020) indicated that the utilization of Edmodo had a positive impact on the language proficiency of the participants. It facilitated the development of interaction and communication skills, provided greater opportunities for idea sharing, and fostered the growth of vocabulary and creativity.…”
Section: Introductionmentioning
confidence: 98%